Serogroup Prevalence, Virulence Profile and Antibiotic Resistance of Avian Pathogenic Escherichia coli Isolated from Broiler Chicken - Showkat A. Shah; Masood S. Mir; Shayaib A. Kamil; Majid Shafi; Mudasir A. Rather; Azmat A. Khan; Zahoor A. Wani; Sheikh Adil; Fatmah M. Alqahtani; Majid Alhomrani; Manzoor Wani (Veterinary Sciences, 2025)
Avian pathogenic Escherichia coli (APEC) causes avian colibacillosis, leading to significant economic losses and concerns for food safety in the poultry industry. This study focused on examining the virulence gene profile, antibiotic resistance prevalence, and resistance patterns of APEC isolates. A total of 250 bacterial strains were collected from birds affected by colibacillosis. Serogrouping revealed diverse serotypes, with O2 being the most common (16%), followed by O1, O8, and O76. All isolates tested positive for at minimum one virulence gene, with 7.2% carrying all five targeted genes, particularly in serogroups O1, O8, O45, and O88. The most detected gene was iss, present in 79.6% of isolates, followed by tsh, iucC, sitA, and papC. The antibiotic resistance analysis showed that all isolates exhibited multidrug resistance, although they remained susceptible to gentamicin, amikacin, ciprofloxacin, and chloramphenicol. Moreover, specific antibiotic resistance genes were known in the isolates, with tetA detected in 54.8%, tetB in 51.7%, sul1 in 50%, and aadA1 in 29.2%. These findings highlight the widespread antibiotic resistance in chicken carcasses, which poses a hazard to human health in terms of transfer of resistance to humans, reduced effectiveness of antibiotics and impaired ability to contain infectious diseases. Therefore, it is crucial to implement strict monitoring programs to regulate antibiotic usage in poultry production.